The impact of leg position on muscle blood flow and oxygenation during low-intensity rhythmic plantarflexion exercise - Kyohei Marume; Hendrik Mugele; Ryo Ueno; Sachin B. Amin; Heru Syarli Lesmana; Carmen Possnig; Alexander B. Hansen; Lydia L. Simpson; Justin S. Lawley (European Journal of Applied Physiology, 2023)
Purpose Resistance training (RT) is an effective countermeasure to combat physical deconditioning whereby localized hypoxia within the limb increases metabolic stress eliciting muscle adaptation. The current study sought to examine the influence of gravity on muscle oxygenation (SmO 2 ) alongside vascular hemodynamic responses. Methods In twelve young healthy adults, an ischemic occlusion test and seven minutes of low-intensity rhythmic plantarflexion exercise were used alongside superficial femoral blood flow and calf near-infrared spectroscopy to assess the microvascular vasodilator response, conduit artery flow-mediated dilation, exercise-induced hyperemia, and SmO 2 with the leg positioned above or below the heart in a randomized order. Results The microvascular vasodilator response, assessed by peak blood flow (798 ± 231 mL/min vs. 1348 ± 290 mL/min; p < 0.001) and reperfusion slope 10 s of SmO 2 after cuff deflation (0.75 ± 0.45%.s-1 vs.2.40 ± 0.94%.s-1; p < 0.001), was attenuated with the leg above the heart. This caused a blunted dilatation of the superficial femoral artery (3.0 ± 2.4% vs. 5.2 ± 2.1%; p = 0.008). Meanwhile, blood flow area under the curve was comparable (above the heart: 445 ± 147 mL vs. below the heart: 474 ± 118 mL; p = 0.55) in both leg positions. During rhythmic exercise, the increase in femoral blood flow was lower in the leg up position (above the heart: 201 ± 94% vs. below the heart: 292 ± 114%; p = 0.001) and contributed to a lower SmO 2 (above the heart: 41 ± 18% vs. below the heart 67 ± 5%; p < 0.001). Conclusion Positioning the leg above the heart results in attenuated peak vascular dilator response and exercise-induced hyperemia that coincided with a lower SmO 2 during low-intensity plantarflexion exercise.

Aortic haemodynamics: the effects of habitual endurance exercise, age and muscle sympathetic vasomotor outflow in healthy men - Denis J. Wakeham; Tony G. Dawkins; Rachel N. Lord; Jack S. Talbot; Freya M. Lodge; Bryony A. Curry; Lydia L. Simpson; Christopher J. A. Pugh; Robert E. Shave; Jonathan P. Moore (European Journal of Applied Physiology, 2022)
Purpose We determined the effect of habitual endurance exercise and age on aortic pulse wave velocity (aPWV), augmentation pressure (AP) and systolic blood pressure (aSBP), with statistical adjustments of aPWV and AP for heart rate and aortic mean arterial pressure, when appropriate. Furthermore, we assessed whether muscle sympathetic nerve activity (MSNA) correlates with AP in young and middle-aged men. Methods Aortic PWV, AP, aortic blood pressure (applanation tonometry; SphygmoCor) and MSNA (peroneal microneurography) were recorded in 46 normotensive men who were either young or middle-aged and endurance-trained runners or recreationally active nonrunners (10 nonrunners and 13 runners within each age-group). Between-group differences and relationships between variables were assessed via ANOVA/ANCOVA and Pearson product-moment correlation coefficients, respectively. Results Adjusted aPWV and adjusted AP were similar between runners and nonrunners in both age groups (all, P > 0.05), but higher with age (all, P < 0.001), with a greater effect size for the age-related difference in AP in runners (Hedges’ g , 3.6 vs 2.6). aSBP was lower in young ( P = 0.009; g = 2.6), but not middle-aged ( P = 0.341; g = 1.1), runners compared to nonrunners. MSNA burst frequency did not correlate with AP in either age group (young: r = 0.00, P = 0.994; middle-aged: r = − 0.11, P = 0.604). Conclusion There is an age-dependent effect of habitual exercise on aortic haemodynamics, with lower aSBP in young runners compared to nonrunners only. Statistical adjustment of aPWV and AP markedly influenced the outcomes of this study, highlighting the importance of performing these analyses. Further, peripheral sympathetic vasomotor outflow and AP were not correlated in young or middle-aged normotensive men.

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)